Immunoreactive dynorphin B in sacral primary afferent fibers of the cat - Basbaum, AI (J Neurosci, 1986)
Immunocytochemical analysis of the distribution of dynorphin B terminals in the sacral spinal cord of the cat revealed a pattern of staining very similar to that produced with antisera directed against the primary afferent derived, putative neurotransmitter, vasoactive intestinal polypeptide. Labeled axons and terminals were concentrated in lamina I and V and there was dense fiber staining in the tract of Lissauer. Of particular interest was the presence of immunoreactive axons in attached dorsal rootlets. To specifically focus on the possibility that some of the sacral primary afferent fibers are dynorphin-immunoreactive, we first tried to increase perikaryal labeling in the sacral dorsal root ganglia by topical treatment with colchicine. This did not produce immunoreactive labeling of cell bodies in the ganglia. Unilateral multiple dorsal rhizotomy (L5 to coccygeal 1), however, significantly decreased the staining of dynorphin- immunoreactive axons and terminals in the tract of Lissauer and in the dorsal horn of sacral segments ipsilateral to the deafferentation. No changes were detected in the lumbar cord. Finally, radioimmunoassay of caudal lumbar and sacral dorsal root ganglia was performed. Measurable immunoreactivity was found in all ganglia assayed, but, consistent with the histochemical analysis, sacral ganglia contained the highest concentration of immunoreactive dynorphin B. These data indicate that a significant component of the sacral spinal cord dynorphin terminal immunoreactivity derives from primary afferent fibers.(ABSTRACT TRUNCATED AT 250 WORDS)